Acute morphine administration alters the power of local field potentials in mesolimbic pathway of freely moving rats: Involvement of dopamine receptors. (1st November 2018) - Ahmadi Soleimani, S. Mohammad; Mohamadi M.A.H, Mohammad Hossein; Raoufy, Mohammad Reza; Azizi, Hossein; Nasehi, Mohammad; Zarrindast, Mohammad Reza
Highlights: Morphine potentiates the LFP power of all frequency bands in rat VTA. Morphine does not alter the LFP power of most frequency bands in rat NAc shell. Morphine reduces the LFP power of theta band in rat NAc shell. The observed morphine-induced effect in VTA is mediated by dopamine receptors. Abstract: Increasing number of evidence support the role of ventral tegmental area (VTA) and nucleus accumbens (NAc) in mediating the opiate effects as the two critical components of brain reward pathway. It is believed that VTA to NAC dopaminergic projections mediate the reinforcing effects induced by opioid drugs. Although numerous studies have investigated mechanisms of reward processing in these brain regions, alterations of local field potentials (LFPs), as an index of total synaptic currents, has not been previously addressed. In the present study, thin metal electrodes were implanted in both VTA and shell sub-region of NAc to simultaneously record the spontaneous LFPs in freely moving rats. After one week recovery period, a single dose of morphine was systemically administered and the LFP recording was performed 15, 30, 45 and 60 post-injection. Also, in order to assess the role of dopamine system, two groups of animals were pre-treated by selective antagonists of dopamine type-1 and type-2 receptors 15 min prior to morphine injection. The obtained results indicated that in VTA, acute morphine administration potentiates the power of all LFP frequency bands (i.e. delta, theta, alpha, beta and gamma). However, in NAc shell, theta wave was significantly attenuated by morphine and other components were not affected. In addition, pre-treatment with both antagonists prevented the observed effect of morphine on LFP power suggesting the involvement of dopamine receptors in this process. Future studies should address mechanisms of dopamine-morphine interactions. It is also valuable to focus on acute and chronic effects of morphine on LFP power and assessment of the observed effects following naloxone challenge.